Pengaruh Aktiva Produktif, Kecukupan Modal, dan LDR Terhadap Kinerja Keuangan Dengan NPL Sebagai Variabel Moderasi - Dwi Apriyantari, Ni Kadek; Ramantha, I Wayan (E-Jurnal Akuntansi, 2018)
To overcome these obstacles, in the community has grown and developed many non-bank financial institutions that conduct business services business development and community empowerment. The data used in this study is secondary data, data taken from annual reports of 35 LPDs registered in LPLPD for 3 years period 2014-2016. Testing data done by using statistical analysis that is Moderated Regression Analysis, test of determination, kelayakn model, hypothesis test. T test is used to test the influence of independent variables partially to dependent variable. Based on the results of the research, it is known that productive assets have an effect on financial performance, capital adequacy has a positive effect on financial performance, and LDR has a positive effect on financial performance. The study also found that NPLs are able to moderate the influence of productive assets, and LDR on financial performance. Keywords : Financial Performance, Earning Assets, Capital Adequacy, Loan To Deposit Ratio, Non Performing Loan